Preliminary Studies : Digital-Based Family Health Education on Prevention of Anemia in Junior High School Students - Ningrum, Dedah; Hufad, Achmad; Wahyudin, Uyu; Suryadi, Ace (Jurnal Paedagogy, 2024)
This study aims to describe a digital-based family health education model for the prevention of anemia in Junior High School Students. This study used a descriptive method with a quantitative approach involving 100 families of female students, who filled out questionnaires regarding their knowledge of anemia, health education, use of digital media, and knowledge and compliance with consuming iron tablets. The data analysis technique in this research used frequency distribution. The results showed that most families lacked knowledge about the signs, consequences, and prevention of anemia, although almost all respondents recognized the importance of family education for anemia prevention. In addition, almost all Junior High School Students had good knowledge of anemia, and almost all families had access and use of WhatsApp as digital media. However, the compliance of Junior High School Students in consuming iron tablets needed improvement. These findings highlight the need for developing a digital-based family health education program utilizing WhatsApp to enhance knowledge and compliance in anemia prevention. It is hoped that this intervention will create sustainable behavioral changes and positively impact the health of adolescent girls.